If it's not what You are looking for type in the equation solver your own equation and let us solve it.
12c-20=4(2c-1)
We move all terms to the left:
12c-20-(4(2c-1))=0
We calculate terms in parentheses: -(4(2c-1)), so:We get rid of parentheses
4(2c-1)
We multiply parentheses
8c-4
Back to the equation:
-(8c-4)
12c-8c+4-20=0
We add all the numbers together, and all the variables
4c-16=0
We move all terms containing c to the left, all other terms to the right
4c=16
c=16/4
c=4
| 7b+3=5b+14 | | 9-6x-5-15x=7 | | n+40=n-40 | | -2n-8-2=9n | | 5p–7=2p+11 | | x+-84=-55 | | 9+4t=-3+6t | | 5k=(-2-8k)-7 | | 7x+62=3x+90 | | 1x=224 | | 8(2x)=28 | | 5a-7=a-15 | | 6x+25-x=32+13 | | 2x+3+4x5=32 | | 5r=(-3r-9)-7 | | 4x-22x=17 | | 6g+5=-2-4g | | -5f-8=6f+4 | | 2m-10=7m | | 4x-6=3+3 | | 6x+8=7-2x | | –2x+10=4x–2 | | –2p+10=4p–2 | | 3c–1=c+9 | | 100(z-0.2=-10(5z+0.8) | | 6x-2=(4x+5)+25 | | 3x+27=5 | | 2x+8=5x+3.5 | | 50+5.5x=18.50+7.75 | | 15+c=19.50 | | 8b+8=6+6b | | k/6+8=5k/6+8=5 |